Óleos essenciais de orégano e alecrim na prevenção e no tratamento da diarréia neonatal em leitões - Luchese, Franciele Camila (2009)
The present study checks the preventive and therapeutic effect of the liquid emulsion of a mixture of essential oils of oregano (Origanum vulgare) and rosemary (Rosmarinus officinalis) in the control of the neonatal diarrhea in sucking piglets of same (therapeutic) diarrheic litter and without clinical demonstration of diarrhea (preventively), born of females with varied orders of childbirth, these animals were divided in two groups, being that the first group of the essential therapeutic oils (GOET) was divided in three treatments: the treatment controls that contained 63 piglets that received 2mL kg 1 of physiologic solution; the treatment with essential oils of oregano (60 % of carvacrol and 15 % thymol and 2 % of essential oil of rosemary) with 148 piglets, which received the liquid emulsion to 5 % in the dose of 2mL kg 1 and the treatment with antibiotic (enrofloxacin) that contained 124 piglets that received to dosage of 1mL 5kg-1 of lively weight of the antimicrobial one. The second group of the preventive essential oils (GOEP) was divided in two treatments: the control treatment that contained 661 piglets that received 1 mL kg 1 physiologic solution and the treatment of essential oils of oregano (60 % of carvacrol and 15 % thymol) and 2 % of essential oil of rosemary that had 672 animals that received the liquid emulsion to 5 % in the dose of 1mL kg 1. The treatments of the group GOET were administered orally during three consecutive days from the confirmation of the demonstration of the clinical signs of diarrhea and for the treatments of the GOEP were administered orally the target medicines from the confirmation of non demonstration of the clinical signs of diarrhea, during the first and third thing days of pig s life. The experimental delineation was of blocks at random for the GOET and for GOEP was composed by two simple treatments, being that for the parameters cure rate and mortality rate of piglets (rates analyzed inside both groups), each animal represented a repetition. The results allowed to conclude that the antibiotic enrofloxacin can be a total substituted by mixture of essential oils for the GOET, on the other hand for the GOEP the results define that the mixture of essential oils with rosemary and oregano s base do not prevent the neonatal diarrheas of the piglets.